2009
DOI: 10.1002/mds.22665
|View full text |Cite
|
Sign up to set email alerts
|

Substantia nigra echogenicity: A structural correlate of functional impairment of the dopaminergic striatal projection in Parkinson's disease

Abstract: Transcranial sonography (TCS) reveals abnormal spatial extension of substantia nigra (SN) echogenicity in a high proportion of patients with Parkinson's disease (PD). It has been proposed that this abnormality represents a structural trait that is mechanistically distinct from degeneration of dopaminergic nigrostriatal projection neurons. We sought to clarify the relationship between sonographic abnormalities of SN and dysfunction of striatal dopaminergic neurotransmission. We studied 50 patients with PD. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 39 publications
(59 reference statements)
3
33
2
Order By: Relevance
“…Recent work by Weise D et al [18] found that extension of SN echogenicity correlated with striatal activity of the presynaptic dopaminergic transporter in PD patients, however, another study determined that SN echogenicity remained the same in a 5-year follow up period,…”
Section: Discussionmentioning
confidence: 94%
“…Recent work by Weise D et al [18] found that extension of SN echogenicity correlated with striatal activity of the presynaptic dopaminergic transporter in PD patients, however, another study determined that SN echogenicity remained the same in a 5-year follow up period,…”
Section: Discussionmentioning
confidence: 94%
“…Enlarged echogenicity in healthy individuals was associated with impaired uptake of [18F]-dopa in the basal ganglia (assessed by positron emission tomography). 10 Substantia nigra echogenicity was correlated to presynaptic dopaminergic dysfunction elicited by single photon emission computed tomography in patients with Parkinson disease 16 and with the severity of parkinsonism induced by neuroleptics in patients with schizophrenia. 17 However, there is still disagreement about how abnormal extension of substantia nigra echogenicity is related to the pathogenic substrate of Parkinson disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that at least during an observational period of 5 years the area of SN hyperechogenicity does not vary by large [40] , and there does not seem to be correlation of disease progression as evidenced by a reduction in tracer uptake on DATScan examinations and extension of ultrasound signal [6] . Still, the relation of ultrasound signal extension and reduced tracer uptake visualized by different functional neuroimaging techniques deserves further evaluation as results are not consistent [41,42] .…”
Section: Tcs In the Early Diagnosis Of Pdmentioning
confidence: 98%